2005
DOI: 10.1159/000092752
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression and Regulation of Chicken Ovalbumin Upstream Promoter Transcription Factors (COUP-TFII and EAR-2) in the Rat Anterior Pituitary Gland

Abstract: Chicken ovalbumin upstream promoter transcription factors (COUP-TF)-II (NR2F2) and EAR-2 (NR2F6) are structurally related orphan members of the nuclear receptors superfamily. There are growing evidences that these factors play important roles during processes of differentiation and proliferation of several tissues. To better understand their role in the differentiated adult rat pituitary gland, we cloned COUP-TFII and EAR-2 cDNAs from an anterior pituitary cDNA library. Subsequently, we raised and characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The Drosophila Seven‐up ( Svp ) gene, encoding the COUP‐TF ortholog, determines photoreceptor cell fate [19], controls cell proliferation in Malpighian tubules [20], and inhibits ecdysone‐dependent transcription [18]. Important roles of COUP‐TF/Svp in neurogenesis, organogenesis and embryogenesis have been illustrated in mammals, chicken, zebrafish, frog and insects [12,14,18,21–23]. More recently, its involvement in regulating mobilization and utilization of glycogen and lipid in skeletal muscle cells has been reported [24–26].…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila Seven‐up ( Svp ) gene, encoding the COUP‐TF ortholog, determines photoreceptor cell fate [19], controls cell proliferation in Malpighian tubules [20], and inhibits ecdysone‐dependent transcription [18]. Important roles of COUP‐TF/Svp in neurogenesis, organogenesis and embryogenesis have been illustrated in mammals, chicken, zebrafish, frog and insects [12,14,18,21–23]. More recently, its involvement in regulating mobilization and utilization of glycogen and lipid in skeletal muscle cells has been reported [24–26].…”
Section: Discussionmentioning
confidence: 99%
“…Chicken ovalbumin upstream promoter transcription factors (COUP-TFs) are highly conserved across species [149] and bind promiscuously to a wide range of direct GGTCA repeat with different spacing and orientations, repressing gene expression either by active repression or by competition for binding sites of other transcription factor [46,150]. COUP-TFα is highly expressed in neuronal tissues of the central and peripheral nervous systems, whereas COUP-TFβ is mainly expressed during embryonic development to regulate neural, muscular, bone, liver and skin differentiation [151].…”
Section: Chicken Ovalbumin Upstream Promoter Transcription Factors (Cmentioning
confidence: 99%
“…COUP-TFα is highly expressed in neuronal tissues of the central and peripheral nervous systems, whereas COUP-TFβ is mainly expressed during embryonic development to regulate neural, muscular, bone, liver and skin differentiation [151]. COU-TFs have lineage-restricted distribution in the normal pituitary, with COUP-TFα expressed exclusively in normal corticotrophs, whereas COUP-TFβ and COUP-TFγ are expressed predominantly in lactotrophs [149]. In contrast, human corticotroph tumors did not express COUP-TFα, suggesting a possible role for COUP-TFα in dysregulated corticotroph cells [45].…”
Section: Chicken Ovalbumin Upstream Promoter Transcription Factors (Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the anterior pituitary gland, COUP-TFI has been detected in the gonadotrope and somatotrope cells, with COUP-TFII expression in the gonadotropes and lactotropes. 41,42 Although they most commonly inhibit promoter activity, they may also stimulate gene expression depending on promoter and cellular context. [43][44][45] Supporting the functional importance of these factors in the gonadotrope, we have reported that siRNA-mediated decreases in endogenous COUP-TFI or COUP-TFII expression blunt a-subunit, LHb-, FSHb-, and GnRHR messenger RNA (mRNA) levels in the LbT2 cell line.…”
Section: Introductionmentioning
confidence: 99%